Analysis of The Effect Caused by Vibration Due to Fiber Bragg Grating Sensor Wavelength - Wahyuningtyas, Firda; Rakhmania, Amalia Eka; Isnomo, Yoyok Heru Prasetyo (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
It is undeniable that fiber cables that are routed underground using the ducting method are susceptible to interference due to external factors such as vibration, especially if the soil is susceptible to vibration activity such as natural factors (earthquakes), heavy traffic, construction, or other human activities. The application of Fiber Bragg Grating sensors along fiber optic cable routes is one solution to facilitate maintenance and checking if data transmission problems occur. In this research, experimental research methods or system creation were used with the aim of the research being to have the final result in the form of an analysis of the influence of object vibrations on the output power and wavelength of the Fiber Bragg Grating Sensor. So, the data obtained in this research can be used as a reference for further research so that Fiber Bragg Grating can be used as a vibration sensor in underground cable routing for data telecommunications systems. The research results show that effective vibration measurements start from load variations of 4 grams to 10 grams and each load variation which is calculated as vibration results in a change in the FBG grating period so that the Bragg wavelength value will also change for each load. As a result of the vibration of the spring, there is a change in the average wavelength of delta lambda Bragg 1.5779 with a system RMS error of 1.19 which indicates the system is working well.